Psychometric Properties of the Urdu Version of Diabetes Knowledge Questionnaire - Bukhsh, Allah; Lee, Shaun Wen Huey; Pusparajah, Priyia; Khan, Amer Hayat; Khan, Tahir Mehmood (Frontiers in Public Health, 2017)
Objective Patient education is a key element in the treatment of diabetes. Assessment of diabetes knowledge is important for optimum treatment. For the assessment of diabetes knowledge, validated tool is essential. None of such validated tool is available in Urdu language. Therefore the aim of this study was to translate and examine the psychometric properties of the-24 item Urdu version of Diabetes Knowledge Questionnaire (DKQ) among type 2 diabetes patients. Methods Standard “forward–backward” process was used to translate DKQ into Urdu language. Later it was validated on a convenience sample of 130 patients with type 2 diabetes, between July and September 2016. Internal consistency was assessed by reliability analysis, One Way Analysis of Variance (ANOVA) was applied for known group validity and Multivariate Linear logistic regression was applied for identifying significant predictors for patients’ DKQ score. Results Good internal consistency was observed for DKQ (Cronbach’s α = 0.702). The mean HbA1C of the patients was 8.55% (±1.91). DKQ scores of patients’ with ‘good glycaemic control’ (14.22±2.4) were observed significantly higher (p<0.05) than patients with ‘poor glycaemic control’ (12.56±2.75). Multiple linear regression revealed that patients’ HbA1c (OR -0.17, CI -1.111, -0.023) and patients’ education (OR 0.17, CI -0.032, 0.758) were significant predictors for DKQ sum score. Conclusion Urdu version of the DKQ is a valid and reliable instrument for adequate estimation disease knowledge and its association with glycaemic control in type 2 diabetes patients in Pakistan.